Incredibly emotional: interpreting trustworthiness in Danish courtrooms - Johansen, Louise Victoria (Frontiers in Sociology, 2024)
This paper explores how Danish legal professionals assess the trustworthiness of victims in criminal cases based on emotional expressions. It focuses on the alignment of these expressions with the nature of the crime, the social context, and the victims’ social identities, and is based on findings from several ethnographic projects involving extensive observations of crime cases and interviews with criminal justice professionals. The research analyzes how victims’ emotional expressions are scrutinized and interpreted within the context of Danish cultural norms, which favor “calm and quiet” behavior. Legal professionals define this behavior as specifically “Danish,” and often contrast it to ethnic minorities’ way of enacting emotions. Emotions are thus culturally and socially interpreted in courtroom settings, and I relate these findings to broader discussions about how emotions mediate, co-create and maintain systematic differences based on gender and ethnicity in legal decision-making. The study thus highlights the cultural and social dimensions of emotions in this legal setting and calls for greater awareness of how these factors influence the assessment of trustworthiness.